PKM Sosialisasi Tanggap Bencana dan Pengelolaan Berkelanjutan dalam Upaya Menjaga Wisata Alam di Desa Gosari - Ahsan, Muhamad; Fitrianto, Achmad Room; Niam, Khoirun; Fitriyah, Ries Dyah; Insiyah, Aslichatul (Universitas Nurul Jadid, 2023)
Gosari Amusing Park (Wagos) is a natural tourism destination located in Gosari Village, Gresik Regency, Indonesia. This community-based research explores an approach that focuses on two crucial aspects: disaster preparedness and sustainable management in the context of village tourism. The primary objectives are to enhance awareness of natural disaster potentials in Wagos while preserving its existence and sustainability as a local entrepreneurship venture.Participatory action research is adopted in three stages in this mentoring program: preparation, implementation, and evaluation. The engagement team, comprising academics, students, and the East Java Regional Disaster Management Agency (BPBD), collaborates with local youth. They work alongside the head of Gosari Village to identify risk mitigation measures, including the installation of evacuation route signs.During the implementation stage, the activities include disaster awareness campaigns, Focus Group Discussions (FGD) to identify vulnerable points, and the introduction of INARISK software along with evacuation simulations for the youth managing Wagos and the Toppi community.The evaluation stage emphasizes the importance of re-socialization by the youth to the local community, the installation of permanent evacuation signs, and impromptu simulations at tourist locations. The results show that the success of disaster risk mitigation heavily depends on community awareness and local entrepreneurship. Wagos, as a tourist village, has proven its existence through the creation of social values and effective promotional efforts. In conclusion, disaster awareness and sustainable management are crucial to maintaining tourist villages in the face of natural disasters and increasing business competition. This community-based research also asserts that an interdisciplinary approach and understanding the local disaster cycle are key to addressing these challenges.